Commodity Liquidity Measurement and Transaction Costs - Marshall, Ben R.; Nguyen, Nhut H.; Visaltanachoti, Nuttawat (Review of Financial Studies, 2012)
[We examine the performance of liquidity proxies in commodities. The Amihud measure has the largest correlation with liquidity benchmarks. Amivest and Effective Tick measures also perform well. These proxies are useful for studies of commodity liquidity over a long time period and those that lack access to high-frequency data. We use various aspects of transaction costs, such as spread, depth, immediacy, and resiliency, to give insight into the costs of different execution approaches. Transaction costs increase with volatility and exhibit mean reversion. Splitting trades over one hour can reduce trading costs by two-thirds compared to an immediate execution.]